Energy Efficiency Methods In Ferrous Melting Foundries -Green House Gas Emissions- A Review - Prof. R. Markandeya, Ch.Parameshwar (International Journal of Scientific Research and Management (IJSRM), 2015)
Iron and steel Industry is the most power consuming industry in India and the world, consuming 25 % of the total industrial power consumption. With consumption of 449.27 Mtoe (million tons of oil equivalent), for total requirement of power generation in India during 2009. The Indian Iron and Steel sector emitted 117.32 Mt CO2 as GHG during 2007. With the ever increasing power consumption and Green House Gases emission, the industrial atmosphere is changing the climate of the earth and Globe resulting directly or indirectly the human activity. The irreversible climate changes are alarmingly changing the global mean temperature which are leading to rise in mean sea levels and change in rain fall patterns. Further, the rise in temperature is warming the Globe and yielding negative impacts on climate, human life, health, food security, economic activity, water resource and physical infrastructure. Farming is under serious effect leading to fall in crop production. Atmosphere change is also leading to tropical deceases and large scale migration .The poorer countries are being worst effected necessitating the world to adopt energy efficient measures to lessen the emission of GHG and to save the Earth. The efficient method applied in the industrial sector not only reduces GHG but also the cost of energy and production of the product. Also have the potential of generating additional revenue through sale of Carbon Credits by making road for Clean Development Mechanism. In this paper, the theoretical quantity of GHG emission is measured from the chemical reactions and Stoichiometry readings for the amount of CO2 generated by combustion of the fuel that is used during the chemical reactions. The emission factors of GHG are calculated basing on the fuel.